Загадкові севрюки: 5. Проблема назви. Територія і стан її заселеності - Балушок, В. (Сiверянський лiтопис, 2016)
У статті ставиться проблема визначення етнонімічної назви севрюків, оскільки
література і джерела дають ряд її різночитань. Також уточнюються межі севрюцької
етнічної території, зокрема, на півдні та південному заході. В статье ставиться проблема определения этнонимического названия севрюков,
поскольку литература и источники дают ряд ее разночтений. Также уточнятся
границы севрюцкой этнической территории, в частности, на юге и юго-западе. There are various forms of the Sevriuk ethnonym in literature: Sevriuks, Sevruks, and
occasionally, Sivriuks. In so doing, sources from Ukraine primarily give the Sevruks form, while
Russian sources customarily contain the form of Sevriuks, which are completely in keeping
with peculiarities of Russian language. However, the Sevruks form corresponds with features
of Northern Ukrainian dialects, as well as the Belarusian language. And the Southeastern
dialect, as far back as at the times of Sevriuks/Sevruks, did not exist yet, therefore we do not
have knowledge of how this ethnonymical appellation would be pronounced in the vernacular
of speakers of this dialect being taken as a basis of Ukrainian literary language.
There has been firmly established an opinion in literature that on Ukrainian territories,
the Sevriuks, particularly in the XVIth–XVIIth centuries, resided only in the utmost East
and on the upper reaches of Left-Bank Ukraine rivers. At the same time, some written and
archaeological sources provide documentary evidence of the fact that although small yet
constant Sevriuk population lived on the whole of Left-Bank Ukraine territory, including the
lower reaches of the rivers of Psel, Vorskla, and Samara, as well as on the riverheads of the
Siverskyi Donets, – to the very Dnipro, except for extreme southern steppe regions.